1993
DOI: 10.1023/a:1018969713547
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Enhanced flux of neutral solutes during transdermal iontophoresis is attributed largely to electroosmotic volume flow. In this study, the iontophoretic fluxes of tritiated water (3H2O) and 14C-labeled mannitol through hairless mouse skin (HMS) were determined. The following questions were addressed: (i) What is the variability of water flux during iontophoresis? (ii) To what extent is the iontophoretic flux of a neutral solute correlated with water flux? (iii) Does the intrinsic permeability of the skin to neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…Wang et al 39 demonstrated that the permeability of hydrocortisone through hairless mouse skin was increased postiontophoretically, suggesting a current-induced effect. Kim et al 58 made the same observation for water and mannitol. Inada et al 38 examined the effects of applied constant voltage on human epidermis in vitro and assessed the ability of the membrane to recover from the electrical perturbation.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Wang et al 39 demonstrated that the permeability of hydrocortisone through hairless mouse skin was increased postiontophoretically, suggesting a current-induced effect. Kim et al 58 made the same observation for water and mannitol. Inada et al 38 examined the effects of applied constant voltage on human epidermis in vitro and assessed the ability of the membrane to recover from the electrical perturbation.…”
Section: Resultsmentioning
confidence: 54%
“…The next 8 h represents the passive transport profiles of LHRH, 12 h postrecovery (see the Experimental following current pretreatment with phosphate-buffered saline for 4 h at current densities of 0.25 and 0.50 mA/ cm 2 . 58 The resulting normalized fluxes were ∼2.5-fold higher than passive diffusion. Pikal and Shah 59 demonstrated that the passive flux of glucose across the skin, after application of the current of 3.2 mA/cm 2 for 3 h, was 10 times greater than before current application.…”
Section: Figure 8seffectmentioning
confidence: 95%
“…Initially targeted were peptides; representative work is that by Green et al [84,85,86,87] providing a first systematic insight into the effects of molecular weight, log partition coefficient and ionization on iontophoretic transport; Langkjaer et al [88] on insulin analogues, Delgado-Charro and Guy [89,90 ]on luteinizing hormone-releasing hormone analogues and Hirvonen and Guy [91 ]and Hirvonen et al [92] on peptides. Due to its high importance in glucose sampling, electro-osmosis was also being investigated by Kim et al [20], and later by Santi and Guy [93,94]. A twist of chance (although Richard asked me to repeat the experiment 3 times before believing the data!)…”
Section: Iontophoresismentioning
confidence: 99%
“…Figure 1 shows Guy's top co-authors and most cited articles [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22]. The Potts and Guy paper ‘Predicting skin permeability' [3] is, of course, the winner.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that any changes in blood glucose concentration are transmitted to the subcutaneous fluid within 5 min [l]. The potential of using iontophoresis as a noninvasive sampling procedure to monitor glucose in humans has been shown recently [2][3][4]. Passive diffusion, however, has been ruled out previously as a method for sampling glucose from the subcutaneous fluid [4].…”
mentioning
confidence: 99%